Vitamin D deficiency in pregnancy – still a public health issue. Issue 1 (11th December 2012) - McAree, Trixie; Jacobs, Benjamin; Manickavasagar, Thubeena; Sivalokanathan, Suganthinie; Brennan, Lauren; Bassett, Paul; Rainbow, Sandra; Blair, Mitch
Abstract: The objectives of this study were to quantify the prevalence of vitamin D insufficiency and deficiency in pregnancy, explore associated risk factors and discuss the public health implications. The study used retrospective analysis of randomly selected data. This is the first report on serum vitamin D levels in an unselected multi‐ethnic population of pregnant women collected between April 2008 and March 2009. Women with sufficient stored serum were randomly selected from among all women who delivered between April 2008 and March 2009. Serum vitamin D levels were determined using liquid chromatography coupled to tandem mass spectrometry. Vitamin D levels were analysed with respect to ethnicity (marking skin tone), calendar quartile, body mass index (BMI), trimester and parity. Deficiency was defined as <25 nmol L −1, insufficiency 25–75 nmol L −1 and adequacy >75 nmol L −1 . Three hundred and forty‐six women were included and represented the total population regarding skin tone, quartile, BMI, gestation and parity. Overall, 18% [95% confidence interval (CI): 15–23%] of sample women had adequate vitamin D levels; 36% were deficient, 45% insufficient. Among women with dark skin, only 8% (95% CI: 5–12%) had adequate levels compared with 43% (95% CI: 33–53%) of those with light skin. Obese women were found have significantly lower vitamin D levels than non‐obese women. Vitamin D deficiency and insufficiency are prevalent year‐round among pregnant women in North West London, especially those with darker skin. Existing supplementation guidelines should be supported; however, other measures are required to improve status among all women.